Potentially commercializable nerve guidance conduits for peripheral nerve injury: Past, present, and future - Chundi Liu; Mouyuan Sun; Lining Lin; Yaxian Luo; Lianjie Peng; Jingyu Zhang; Tao Qiu; Zhichao Liu; Jun Yin; Mengfei Yu (Materials Today Bio)
Peripheral nerve injuries are a prevalent global issue that has garnered great concern. Although autografts remain the preferred clinical approach to repair, their efficacy is hampered by factors like donor scarcity. The emergence of nerve guidance conduits as novel tissue engineering tools offers a promising alternative strategy. This review aims to interpret nerve guidance conduits and their commercialization from both clinical and laboratory perspectives. To enhance comprehension of clinical situations, this article provides a comprehensive analysis of the clinical efficacy of nerve conduits approved by the United States Food and Drug Administration. It proposes that the initial six months post-transplantation is a critical window period for evaluating their efficacy. Additionally, this study conducts a systematic discussion on the research progress of laboratory conduits, focusing on biomaterials and add-on strategies as pivotal factors for nerve regeneration, as supported by the literature analysis. The clinical conduit materials and prospective optimal materials are thoroughly discussed. The add-on strategies, together with their distinct obstacles and potentials are deeply analyzed. Based on the above evaluations, the development path and manufacturing strategy for the commercialization of nerve guidance conduits are envisioned. The critical conclusion promoting commercialization is summarized as follows: 1) The optimization of biomaterials is the fundamental means; 2) The phased application of additional strategies is the emphasized direction; 3) The additive manufacturing techniques are the necessary tools. As a result, the findings of this research provide academic and clinical practitioners with valuable insights that may facilitate future commercialization endeavors of nerve guidance conduits.